Electrocatalyst, preparation method and application thereof

By constructing a multi-shell hollow structure electrocatalyst Ni2P@CoP@NC coated with nitrogen-doped carbon, Ni2P@CoP@NC, the existing electrocatalyst is solved, and the problem of insufficient activity and stability in the water decomposition reaction is achieved, and efficient and stable Electrocatalytic properties.

CN119121303APending Publication Date: 2024-12-13BOZHOU SHANGDA ENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411082239.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing transition metal phosphide electrocatalysts have problems with limited number of active sites, low mass transfer efficiency and poor stability in water decomposition reactions, especially in long-term operation at high current density.

Method used

Ni-gly microspheres are mixed with cobalt salt and 2-methylimidazole in the first solvent, and etched and phosphated by tannin acid to form a multi-shell hollow structure of bimetallic phosphide coated with nitrogen doped carbon. The electrocatalyst Ni2P@CoP@NC is constructed by thermal solvent method and external coating technology.

Benefits of technology

The overall conductivity and catalytic activity of the electrocatalyst is improved, energy loss is reduced, reaction overpotential is significantly reduced, reaction rate is accelerated, and excellent stability and high efficiency are shown in the electrolytic water decomposition process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121303A_ABST
    Figure CN119121303A_ABST
Patent Text Reader

Abstract

The invention provides an electrocatalyst as well as a preparation method and application thereof, a high-performance nitrogen-doped carbon-coated bimetallic phosphide multi-shell hollow structure electrocatalyst (Ni2P-coated CoP-coated NC) is successfully prepared by optimizing the structure and composition of a material, and the technical bottleneck in the field of electrocatalytic water decomposition is solved. Firstly, a unique hot solvent method is combined with an external coating and etching technology, gradual construction from Ni-gly yolk shell microspheres to Ni-gly ZIF-67 and then to a multi-shell hollow structure is achieved, and finally the Ni2P-CoP-NC compound is formed through calcination. Secondly, due to introduction of a nitrogen-doped carbon shell of the electrocatalyst, the overall conductivity of the composite material is effectively improved through a multi-shell hollow structure, rapid transmission of electrons in the catalysis process is ensured, energy loss is reduced, and therefore the catalysis efficiency is improved; the electrocatalyst shows excellent catalytic activity in the electrolytic water decomposition process, the reaction overpotential can be remarkably reduced, and the reaction rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new nano materials, and in particular to a nitrogen-doped carbon-coated bimetallic phosphide multi-shell hollow structure electrocatalyst. Background Art

[0002] As a clean and efficient energy conversion pathway, electrochemical water splitting is widely regarded as one of the key technologies for achieving a sustainable hydrogen economy. The process involves two half reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. These reactions not only form the basis for hydrogen production by water electrolysis, but also provide storage solutions for intermittent renewable energy sources such as solar and wind power. However, the thermodynamic and kinetic characteristics of the water splitting reaction require the use of efficient electrocatalysts to reduce the overpotential, promote the transfer of electrons and protons, and thus improve the energy conversion efficiency.

[0003] At present, iridium (Ir), ruthenium (Ru) and platinum (Pt)-based materials dominate the OER and HER fields due to their excellent electrocatalytic performance. However, the high price and resource scarcity limit the commercialization and large-scale application of these precious metal catalysts. Therefore, finding alternative catalysts with higher cost-effectiveness and more abundant resources has become a research hotspot.

[0004] Transition Metal Phosphides (TMPs) have shown great potential due to their unique electronic structure and enzyme-like activity. Among them, nickel phosphide (Ni2P) and cobalt phosphide (CoP) have become water electrolysis catalysts that have attracted much attention in recent years due to their unique electronic structure, excellent catalytic activity and stability. However, these metal-based phosphides often show excellent HER performance and general OER performance, resulting in insufficient overall water splitting activity, which limits their application in practical water splitting systems.

[0005] To overcome this limitation, constructing nano-heterostructures composed of different electrocatalysts has become an effective strategy to improve the efficiency of water splitting. This structure not only utilizes the strong electronic coupling of the heterogeneous interface to promote the redistribution of electron density, but also creates additional active edges by introducing interfacial defects such as phosphorus vacancies, thereby enhancing the electrocatalytic activity. However, existing heterostructure catalysts still suffer from problems such as limited number of active sites, low mass transfer efficiency and poor stability, especially for long-term operation at high current density. Summary of the invention

[0006] In order to address the deficiencies of the prior art and achieve efficient, stable and cost-effective water decomposition, the present invention provides an electrocatalyst, a preparation method and an application thereof.

[0007] The first aspect of the present invention provides a method for preparing an electrocatalyst, comprising the steps of:

[0008] Provide a Ni-gly microsphere;

[0009] Ni-gly microspheres, cobalt (Co 2+ ) salt and 2-methylimidazole are mixed in a first solvent to obtain Ni-gly@ZIF-67; Ni-gly@ZIF-67 is etched with tannic acid to obtain Ni-gly@ZIF-67-TA;

[0010] Ni-gly@ZIF-67-TA is phosphated to obtain Ni2P@CoP@NC, i.e., the composite electrocatalyst.

[0011] In a preferred embodiment, the Ni-gly microspheres are made of nickel (Ni 2+ ) salt and glycerol, more preferably, the preparation method of the Ni-gly microspheres comprises the following steps:

[0012] Nickel (Ni 2+ ) salt and glycerol are mixed and reacted in a second solvent to obtain Ni-gly microspheres.

[0013] Preferably, the second solvent can be one or more of water, alcohol, ether, ester, ketone, nitrile, halogenated hydrocarbon, aromatic hydrocarbon, and is preferably a mixed solvent selected from: water, N,N-dimethylformamide, methanol, ethanol, isopropanol, ether, tetrahydrofuran, acetonitrile, valeronitrile, methoxypropionitrile, butyronitrile, adiponitrile, benzyl cyanide, chloroacetonitrile, dichloromethane, carbon tetrachloride, ethyl acetate, acetone, N-methylpyrrolidone, toluene or one or more combinations thereof.

[0014] Preferably, the nickel salt may be an inorganic acid salt or an organic acid salt, and is preferably one or more combinations selected from Ni(NO3)2, NiCO3, NiSO4, NiCl2, NiBr2, Ni(CH3COO)2, and Ni(HCOO)2.

[0015] Preferably, the nickel salt may be provided in the form of a hydrate, an aqueous solution or an alcohol solution.

[0016] Preferably, the nickel (Ni 2+ ) The reaction temperature of the salt and glycerol is 120-300°C, preferably 150-250°C, and more preferably 180-200°C.

[0017] Preferably, the nickel (Ni 2+ ) salt and glycerol reaction time is 8-24h, preferably 10-20h, more preferably 15-18h.

[0018] Preferably, the cobalt salt may be an inorganic acid salt or an organic acid salt, and is preferably one or more combinations selected from Co(NO3)2, CoCO3, CoSO4, CoCl2, CoBr2, Co(CH3COO)2, and Co(HCOO)2.

[0019] Preferably, the cobalt salt may be provided in the form of a hydrate, an aqueous solution or an alcohol solution.

[0020] In a preferred embodiment, the Ni-gly microspheres and cobalt (Co 2+ ) salt and 2-methylimidazole are activated before mixing.

[0021] Preferably, the activation of the Ni-gly microspheres comprises the following steps:

[0022] The Ni-gly microspheres were mixed with an ethanol solution of phytic acid to obtain activated Ni-gly microspheres.

[0023] Preferably, in the ethanol solution of phytic acid, the volume ratio of phytic acid to ethanol is 1:(20-80), preferably 1:(30-60), and preferably 1:(40-50).

[0024] Preferably, the activation time of the Ni-gly microspheres is 1-5 h, preferably 1-4 h, and more preferably 2-3 h.

[0025] Preferably, the activation temperature of the Ni-gly microspheres is -10-50°C, preferably -5-40°C, and more preferably 0-35°C.

[0026] Preferably, the first solvent can be one or more of water, alcohol, ether, ester, ketone, nitrile, halogenated hydrocarbon, aromatic hydrocarbon, and is preferably a mixed solvent selected from: water, N,N-dimethylformamide, methanol, ethanol, isopropanol, ether, tetrahydrofuran, acetonitrile, valeronitrile, methoxypropionitrile, butyronitrile, adiponitrile, benzyl cyanide, chloroacetonitrile, dichloromethane, carbon tetrachloride, ethyl acetate, acetone, N-methylpyrrolidone, toluene or one or more combinations thereof.

[0027] Preferably, the Ni-gly microspheres, cobalt (Co 2+ ) salt and 2-methylimidazole are mixed in the first solvent and a dispersant is also added.

[0028] More preferably, the dispersant is selected from one or more combinations of polyvinyl pyrrolidone (PVP), sodium dodecyl sulfate (SDS), polyethylene glycol (PEG), sodium polystyrene sulfonate (PSS), polyacrylic acid (PAA), and polyethyleneimine (PEI).

[0029] Preferably, the Ni-gly microspheres, cobalt salt, and 2-methylimidazole are mixed in a first solvent, and the steps include: mixing the Ni-gly microspheres in part of the first solvent to obtain a first solution;

[0030] Mixing cobalt salt and 2-methylimidazole in a portion of the first solvent to obtain a second solution;

[0031] The first solution is mixed with the second solution.

[0032] More preferably, the second solution is poured into the first solution.

[0033] More preferably, the dispersant is mixed with Ni-gly microspheres in a first solvent to obtain the first solution.

[0034] More preferably, the cobalt salt is mixed in part of the first solvent to obtain a solution A;

[0035] Mixing 2-methylimidazole in a portion of the first solvent to obtain a solution B;

[0036] Solution A and solution B were poured into the first solution respectively and mixed to obtain Ni-gly@ZIF-67.

[0037] In a preferred embodiment, the tannic acid etches Ni-gly@ZIF-67, and the steps include:

[0038] Dispersing Ni-gly@ZIF-67 in a third solvent to obtain a third solution;

[0039] providing a solution of tannic acid dispersed in a third solvent, i.e., a tannic acid solution;

[0040] adding alkali to the tannic acid solution and adjusting the pH value to a preset value to obtain a fourth solution;

[0041] The fourth solution is added to the third solution to react and obtain the Ni-gly@ZIF-67-TA.

[0042] Preferably, the third solvent can be one or more of water, alcohol, ether, ester, ketone, nitrile, halogenated hydrocarbon, aromatic hydrocarbon, and ionic liquid, and is preferably selected from: water, N,N-dimethylformamide, methanol, ethanol, ether, tetrahydrofuran, acetonitrile, valeronitrile, methoxypropionitrile, butyronitrile, adiponitrile, benzyl cyanide, chloroacetonitrile, dichloromethane, carbon tetrachloride, ethyl acetate, acetone, N-methylpyrrolidone, toluene, ionic liquid (such as 1-butyl-3-methylimidazolium hexafluorophosphate) and one or more combinations of solvents mixed.

[0043] Preferably, the tannic acid concentration of the tannic acid solution is 10-50 mmol / L, preferably 15-40 mmol / L, more preferably 24-30 mmol / L.

[0044] Preferably, the base is provided in the form of a solid, an aqueous solution, or an alcoholic solution.

[0045] Preferably, the base is provided in the form of an aqueous solution or an alcohol solution. More preferably, the concentration of the base (in terms of free OH dissolved in the solution) is - The molecular weight of the present invention is 1-10 mol / L, preferably 2-8 mol / L, and more preferably 4-6 mol / L.

[0046] Preferably, the base is selected from one or more of sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), and aqueous ammonia (NH3·H2O).

[0047] Preferably, the preset pH value is 7-14, preferably 8-12, and more preferably 8-10.

[0048] Preferably, the fourth solution is added to the third solution in a dropwise manner.

[0049] Preferably, the Ni-gly@ZIF-67-TA is cleaned before phosphating.

[0050] More preferably, the cleaning solvent used for cleaning the Ni-gly@ZIF-67-TA is one or more of water, ethanol and methanol.

[0051] More preferably, the washed Ni-gly@ZIF-67-TA is further dried.

[0052] More preferably, the drying temperature of the Ni-gly@ZIF-67-TA is 50-100°C, preferably 55-80°C, and more preferably 60-70°C.

[0053] More preferably, the drying time of the Ni-gly@ZIF-67-TA is 8-48 h, preferably 10-36 h, and more preferably 12-24 h.

[0054] In a preferred embodiment, the phosphating step comprises:

[0055] Ni-gly@ZIF-67-TA and phosphate are calcined in a closed environment to obtain Ni2P@CoP@NC, the composite electrocatalyst.

[0056] Preferably, the mass ratio of Ni-gly@ZIF-67-TA to phosphate (with P as the standard) is 1:(2-15), preferably 1:(4-12), and more preferably 1:(6-10).

[0057] Preferably, the phosphate is selected from phosphate (PO4 3- ), phosphite (PO2 - ), hypophosphite (PO2 3- )

[0058] Specifically, the phosphate includes one or more combinations of trisodium phosphate, tripotassium phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, disodium hydrogen phosphate, sodium hypophosphite, potassium hypophosphite, sodium phosphite, and potassium phosphite.

[0059] Preferably, during the calcination process, the phosphate is placed at the upper end of the gas flow, and the Ni-gly@ZIF-67-TA powder is placed at the lower end of the gas flow.

[0060] Preferably, the calcination temperature is 200-500°C, preferably 300-450°C, more preferably 350-400°C.

[0061] Preferably, the calcination time is 60-300 min, preferably 100-200 min, more preferably 120-150 min.

[0062] Preferably, the heating rate of the calcination is 1-5°C / min, preferably 1.5-3°C / min, more preferably 2-2.5°C / min.

[0063] Preferably, the calcination atmosphere is an inert gas.

[0064] More preferably, the inert gas is selected from one or more combinations of nitrogen, argon and helium.

[0065] The second aspect of the present invention is to provide an electrocatalyst having a structure of Ni2P@CoP@NC.

[0066] Preferably, in the electrocatalyst, the mass ratio of Ni2P, CoP and NC is (2-20):1:1, preferably (5-15):1:1, and more preferably (8-10):1:1.

[0067] Preferably, the porosity of the electrocatalyst is 10-55%, preferably 15-50%, more preferably 25-40%.

[0068] Preferably, the pore size of the electrocatalyst is 50-250 nm, preferably 60-200 nm, more preferably 80-150 nm.

[0069] Preferably, the electrocatalyst has a -2 The HER performance is 80-180 mV, preferably 100-150 mV, and more preferably 120-140 mV.

[0070] Preferably, the Tafel slope of the electrocatalyst is 100-120 mVdec -1 , preferably 105-115mVdec -1 , more preferably 110-113mVdec -1 .

[0071] Preferably, the electrocatalyst has an OER performance of 5-15 mA cm at 276 mV. -2 , preferably 6-12mAcm -2 , more preferably 8-10 mA cm -2 .

[0072] Preferably, the electrocatalyst is obtained based on the aforementioned preparation method.

[0073] The third aspect of the present invention provides an application of an electrocatalyst, wherein the electrocatalyst can be applied to water electrolysis, especially hydrogen evolution and / or oxygen evolution reaction.

[0074] In the present application, Ni-gly refers to nickel-based glycerate.

[0075] In this application specification, ZIF-67 refers to Zeolitic Imidazolate Framework-67, which is a metal-organic framework (MOF) material. This material is mainly composed of cobalt ions (Co 2+ ) and 2-methylimidazole, and has a high specific surface area, tunable pore size, controllable metal center and excellent physicochemical stability.

[0076] In this application specification, @ is used to describe the structure of nanomaterials, indicating a coating, core-shell structure or hierarchical relationship in a composite material. Specifically, in Ni2P@CoP@NC, it means that one material (here Ni2P) is coated by another material (here CoP), and the whole is coated or supported by a third material (here NC, i.e., nitrogen-doped carbon material).

[0077] Compared with the prior art, the present invention has the following beneficial technical effects:

[0078] The present invention provides a method for preparing an electrocatalyst. By optimizing the structure and composition of the material, a high-performance nitrogen-doped carbon-coated bimetallic phosphide multi-shell hollow structure electrocatalyst (Ni2P@CoP@NC) is successfully prepared, which solves the technical bottleneck in the field of electrocatalytic water decomposition.

[0079] First, the present invention adopts a unique hot solvent method combined with external coating and etching technology to achieve the gradual construction from Ni-gly yolk shell microspheres to Ni-gly@ZIF-67, and then to multi-shell hollow structures, and finally forms a Ni2P@CoP@NC composite by calcination.

[0080] Secondly, the introduction of the nitrogen-doped carbon shell and the multi-shell hollow structure of the electrocatalyst of the present invention effectively improves the overall conductivity of the composite material, ensures the rapid transmission of electrons in the catalytic process, reduces energy loss, and thus improves the catalytic efficiency, so that the electrocatalyst exhibits excellent catalytic activity in the process of electrolytic water decomposition, can significantly reduce the reaction overpotential, and accelerate the reaction rate.

[0081] In addition, the electrocatalyst preparation method of the present invention is simple, controllable, and easy to achieve large-scale production. The prepared catalyst has broad application prospects in the field of water electrolysis hydrogen production, and provides new ideas and directions for the development of efficient and stable hydrogen energy conversion and storage materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] Figure 1 This is the XRD diffraction pattern of Ni2P@CoP@NC obtained in Example 1 of the present invention.

[0083] Figure 2 In the figure, (a) is the Raman spectrum of Ni2P@CoP@NC obtained in Example 1 of the present invention; (b) is the electron paramagnetic resonance image of Ni2P@CoP@NC obtained in Example 1 of the present invention.

[0084] Figure 3 In the figure, (a) is a cyclic voltammogram of hydrogen evolution reaction of Ni2P@CoP@NC obtained in Example 1 of the present invention; (b) is a cyclic voltammogram of hydrogen evolution reaction of Ni2P@C obtained in Comparative Example 1 of the present invention; (c) is a cyclic voltammogram of hydrogen evolution reaction of CoP@NC obtained in Comparative Example 2 of the present invention; (d) is a cyclic voltammogram of hydrogen evolution reaction of Pt / C obtained in Comparative Example 3 of the present invention; (e) is a cyclic voltammogram of hydrogen evolution reaction of NF obtained in Comparative Example 4 of the present invention; (f) is a double layer capacitance curve C of Ni2P@CoP@NC, Ni2P@C, CoP@NC, Pt / C, and NF obtained in Example 1 and Comparative Examples 1-4 of the present invention. dl , the horizontal axis is the scanning frequency (scan rate).

[0085] Figure 4In the figure, (a) is the HER polarization curves of Ni2P@CoP@NC, Ni2P@C, CoP@NC, Pt / C, and NF obtained in Example 1 of the present invention and Comparative Examples 1-4, where the abscissa is potential and the ordinate is current density; (b) is the Tafel slope of Ni2P@CoP@NC, Ni2P@C, CoP@NC, Pt / C, and NF obtained in Example 1 of the present invention and Comparative Examples 1-4, where the ordinate is overpotential; (c) is the HER polarization curves of Ni2P@CoP@NC, Ni2P@C, CoP@NC, Pt / C, and NF obtained in Example 1 of the present invention and Comparative Examples 1-4 at 10 mA cm -2 Overpotential column and Tafel slope graph under current density; (d) Ni2P@CoP@NC obtained in Example 1 of the present invention at 10 mA cm -2 The chronoamperometric curve below.

[0086] Figure 5 In the figure, (a) is the OER polarization curves of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 of the present invention and Comparative Examples 1, 2, 4, and 5; (b) is the Tafel slope of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 of the present invention and Comparative Examples 1, 2, 4, and 5; (c) is the Tafel slope of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 of the present invention and Comparative Examples 1, 2, 4, and 5 at 20 mA cm -2 Overpotential column and Tafel slope graph under current density; (d) is the double layer capacitance curve (C) of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 and Comparative Examples 1, 2, 4, and 5 of the present invention. dl ); (e) is the Nyquist diagram and simulated equivalent circuit diagram of Ni2P@CoP@NC, Ni2P@C, and CoP@NC obtained in Example 1 of the present invention, Comparative Examples 1 and 2; (f) is the Ni2P@CoP@NC obtained in Example 1 of the present invention at 20mA cm -2 The chronoamperometric curve below.

[0087] Figure 6 In the figure, (a) is the cyclic voltammogram of oxygen evolution reaction of Ni2P@CoP@NC obtained in Example 1 of the present invention; (b) is the cyclic voltammogram of oxygen evolution reaction of Ni2P@C obtained in Comparative Example 1 of the present invention; (c) is the cyclic voltammogram of oxygen evolution reaction of CoP@NC obtained in Comparative Example 2 of the present invention; (d) is the cyclic voltammogram of oxygen evolution reaction of NF obtained in Comparative Example 4 of the present invention; (e) is the cyclic voltammogram of oxygen evolution reaction of RuO2 obtained in Comparative Example 5 of the present invention.

[0088] Figure 7 In the figure, (a) is the polarization curve of the electrolytic cell of Ni2P@CoP@NC / / Ni2P@CoP@NC obtained in Example 1 of the present invention, and Pt / C / / RuO2 obtained in Comparative Examples 3 and 5; (b) is the full water decomposition stability of Ni2P@CoP@NC / / Ni2P@CoP@NC obtained in Example 1 of the present invention, and Pt / C / / RuO2 obtained in Comparative Examples 3 and 5. DETAILED DESCRIPTION

[0089] The embodiments of the present invention provide an electrocatalyst, a preparation method and an application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0090] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged under appropriate circumstances. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0091] Example 1

[0092] This embodiment provides a method for preparing Ni2P@CoP@NC, the steps comprising:

[0093] (1) Preparation of precursor nickel-based glycerate spheres (Ni-gly): 0.07 g Ni(NO3)2·6H2O was added to 20 mL isopropanol, and after being dispersed uniformly by ultrasound, 4 mL glycerol and 1 mL water were added respectively. After stirring for 20 minutes, the mixture was transferred to a 50 mL Telfon-lined autoclave and reacted in an oven at 200°C for 15 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and finally dried in a vacuum oven. The collected product was Ni-gly microspheres.

[0094] (2) Preparation of ZIF-67 coated Ni-gly microsphere composite structure (Ni-gly@ZIF-67): Take 40 mg of Ni-gly and disperse it in 40 mL of ethanol. Pour 10 mL of phytic acid ethanol solution (volume ratio of 1:40) into the above dispersion and stir for 2 hours. This process is to activate the Ni-gly microspheres. Then wash them with ethanol and methanol respectively, and then directly disperse them in 25 mL of methanol after washing. Add 1 g of polyvinyl pyrrolidone (PVP) and stir for 10 minutes, and let it stand for 15 minutes. Dissolve 0.20 g of Co(NO3)2·6H2O in 30 mL of methanol to prepare solution A, and dissolve 2.96 g of dimethylimidazole (2-MIM) in 60 mL of methanol to prepare solution B. Pour solutions A and B into the above-mentioned stationary solutions respectively and stir them together for 2.5 hours. After centrifugation, washing with methanol and drying, purple powder of ZIF-67-coated Ni-gly microspheres was obtained, which was recorded as Ni-gly@ZIF-67.

[0095] (3) Preparation of Ni-gly@ZIF-67-TA multi-shell hollow nanoparticles: 100 mg of Ni-gly@ZIF-67 powder was dissolved in 5 mL of water and dispersed evenly by ultrasonication. 6 mL of tannic acid (TA) solution (24 mmol / L) was adjusted to pH 8 with KOH solution (6 mol / L). The pH-adjusted solution was added dropwise to the above solution and magnetically stirred for 10 min at room temperature to obtain Ni-gly@ZIF-67-TA. The solution was centrifuged, washed with ethanol and water, respectively, and dried in a vacuum oven at 60 °C.

[0096] (4) Preparation of Ni2P@CoP@NC: 350 mg of sodium hypophosphite and 35 mg of Ni-gly@ZIF-67-TA powder were placed in a porcelain boat. The sodium hypophosphite was placed at the upper end of the airflow and the Ni-gly@ZIF-67-TA powder was placed at the lower end of the airflow. The mixture was calcined at 350°C for 2 h at a heating rate of 2°C / min under N2 atmosphere to obtain a black powder, which was recorded as Ni2P@CoP@NC.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing Ni2P@C, the steps comprising:

[0099] (1) Preparation of precursor nickel-based glycerate spheres (Ni-gly): 0.07 g Ni(NO3)2·6H2O was added to 20 mL isopropanol, and after being dispersed uniformly by ultrasound, 4 mL glycerol and 1 mL water were added respectively. After stirring for 20 minutes, the mixture was transferred to a 50 mL Telfon-lined autoclave and reacted in an oven at 200°C for 15 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and finally dried in a vacuum oven. The collected product was Ni-gly microspheres.

[0100] (2) Preparation of Ni-gly-TA: 100 mg of Ni-gly powder was dissolved in 5 mL of water and dispersed evenly by ultrasonication. 6 mL of tannic acid (TA) solution (24 mmol / L) was adjusted to pH 8 with KOH solution (6 mol / L). The pH-adjusted solution was added dropwise to the above solution and magnetically stirred for 10 minutes at room temperature to obtain Ni-gly-TA. The solution was centrifuged, washed with ethanol and water, respectively, and dried in a vacuum drying oven at 60°C.

[0101] (3) Preparation of Ni2P@C: 350 mg of sodium hypophosphite and 35 mg of Ni-gly-TA powder were placed in a porcelain boat. The sodium hypophosphite was placed at the upper end of the airflow and the Ni-gly-TA powder was placed at the lower end of the airflow. The mixture was calcined at 350°C for 2 hours at a heating rate of 2°C / min under N2 atmosphere to obtain a black powder, which was recorded as Ni2P@C.

[0102] Comparative Example 2

[0103] This comparative example provides a method for preparing CoP@NC, the steps comprising:

[0104] (1) Preparation of ZIF-67: 0.20 g of Co(NO3)2·6H2O was dissolved in 30 mL of methanol to prepare solution A, and 2.96 g of dimethylimidazole (2-MIM) was dissolved in 60 mL of methanol to prepare solution B. Solutions A and B were mixed and stirred for 2.5 hours. The mixture was centrifuged, washed with methanol, and dried to obtain ZIF-67.

[0105] (2) Preparation of ZIF-67-TA: 100 mg of ZIF-67 powder was dissolved in 5 mL of water and dispersed evenly by ultrasonication. 6 mL of tannic acid (TA) solution (24 mmol / L) was adjusted to pH 8 with KOH solution (6 mol / L). The pH-adjusted solution was added dropwise to the above solution and magnetically stirred for 10 minutes at room temperature to obtain ZIF-67-TA. The solution was centrifuged, washed with ethanol and water respectively, and dried in a vacuum drying oven at 60°C.

[0106] (3) Preparation of CoP@NC: 350 mg of sodium hypophosphite and 35 mg of ZIF-67-TA powder were placed in a porcelain boat. The sodium hypophosphite was placed at the upper end of the airflow and the ZIF-67-TA powder was placed at the lower end of the airflow. The mixture was calcined at 350 °C for 2 h at a heating rate of 2 °C / min under N2 atmosphere to obtain a black powder, which was recorded as CoP@NC.

[0107] Comparative Example 3

[0108] This comparative example provides a Pt / C electrode, wherein the model of the Pt / C electrode is a standard Pt / C electrode of the electrochemical workstation CHI 660E of Shanghai Chenhua Instrument Co., Ltd.

[0109] Comparative Example 4

[0110] This comparative example provides a NF, where NF is the abbreviation of Ni Foam, which refers to nickel foam.

[0111] The preparation method of the NF is that the catalyst can be loaded after pretreatment.

[0112] The pretreatment steps include: cutting the nickel foam into pieces of 1×2 cm 2 The sheets were ultrasonically treated in 3M HCl solution, ethanol and deionized water for 30 minutes each in sequence to completely clean the surface impurities, and finally dried under vacuum.

[0113] Comparative Example 5

[0114] This comparative example provides a RuO2, the model of which is the standard RuO2 electrode of the electrochemical workstation CHI 660E of Shanghai Chenhua Instrument Co., Ltd.

[0115] Figure 1 This is the XRD diffraction pattern of Ni2P@CoP@NC obtained in Example 1 of the present invention. It can be seen from the figure that its XRD peaks match well with Ni2P (JCPDS#03-0953) and CoP (JCPDS#29-0497). It can be seen from the figure that the peaks at 40.8°, 44.6°, 47.3°, 54.2°, 54.9° and 74.7° correspond to the (111), (201), (210), (300), (211) and (400) crystal planes of Ni2P; and the peaks at 31.6°, 36.3°, 46.2°, 48.1°, 56.8° correspond to the (011), (111), (112), (211) and (301) crystal planes of CoP. The results show that Ni2P and CoP coexist in the sample obtained in the present invention, which is a composite material of Ni2P and CoP.

[0116] Figure 2The Raman spectrum (Figure a) and the electron paramagnetic resonance spectrum (Figure b) of Ni2P@CoP@NC obtained in Example 1 of the present invention are shown in Figure a. -1 Two characteristic bands related to the D and G bands of carbon materials were observed at D / I G ) is 0.92, indicating that defects or disordered sites are formed in the carbon shell. Such a carbon shell is not only beneficial to the electrocatalytic stability of Ni2P, but also beneficial to improving the electrochemical performance of the composite material, because defective carbon has higher π bonds and electron donor-acceptor characteristics. Raman results confirm the carbon shell coated on the outer layer of the composite material. As shown in Figure b: Electron paramagnetic resonance (ESR) shows the existence of P vacancies. The fluctuation at g≈2.004 indicates the presence of lattice vacancies, and P vacancies can increase active sites and adjust the electron density in the center of the active site, thereby expanding the electrochemical active area, accelerating electron transport and promoting electron coupling effects, and promoting electrocatalytic reactions.

[0117] Figure 3 In the figure, (a) is the cyclic voltammogram of hydrogen evolution reaction of Ni2P@CoP@NC obtained in Example 1 of the present invention; (b) is the cyclic voltammogram of hydrogen evolution reaction of Ni2P@C obtained in Comparative Example 1 of the present invention; (c) is the cyclic voltammogram of hydrogen evolution reaction of CoP@NC obtained in Comparative Example 2 of the present invention; (d) is the cyclic voltammogram of hydrogen evolution reaction of Pt / C obtained in the present invention, (e) is the cyclic voltammogram of hydrogen evolution reaction of NF obtained in the present invention; (f) is the double layer capacitance curve C of Ni2P@CoP@NC, Ni2P@C, CoP@NC, Pt / C and NF obtained in Example 1 and Comparative Examples 1-4 of the present invention dl The catalytic activity of Ni2P@CoP@NC multi-shell hollow catalyst in 1M KOH alkaline electrolyte was tested using a standard three-electrode system, and its HER (hydrogen evolution reaction) performance was analyzed. Under the same conditions, the electrocatalytic performance of Ni2P@C, CoP@NC, commercial Pt / C and pure nickel foam (NF) was also tested. As shown in the figure: in the non-Faraday region, 10mV s -1 , 20mV s -1 , 40mV s -1 , 80mV s -1 , 100mV s -1 , five different scanning rates of cyclic voltammetry tests, and the CV curves of the tested samples were obtained. The electrochemical double layer capacitance (C dl ), which can be used to determine the electrochemically active surface area (ECSA) of the material. As shown in FIG. f, it can be seen from the figure that the C dl 2.57mF cm -2, higher than Ni2P@C (1.56mF cm -2 ) and CoP@NC (1.37 mF cm -2 ), indicating that the unique multi-shell hollow structure has a larger surface area, providing more electrocatalytic active sites for its HER reaction.

[0118] Figure 4 HER polarization curve (Figure a), Tafel slope (Figure b), and 10 mA cm-2 of Ni2P@CoP@NC obtained in Example 1 of the present invention -2 Overpotential column and Tafel slope graph under current density (Figure c), Ni2P@CoP@NC at 10mA cm -2 Figure d shows the chronoamperometric curve under the condition of HER correction. Figure a shows the LSV curve after iR correction. Compared with Ni2P and CoP, Ni2P@CoP@NC catalyst exhibits better HER catalytic activity, reaching 10 mA cm at a low overpotential of 147 mV. -2 However, the single-layer hollow Ni2P@C and CoP@NC have limited catalytic sites, resulting in poor alkaline HER activity, requiring 221mV and 196mV to reach 10mAcm, respectively. -2 Current density. Figure b is the corresponding Tafel slope diagram obtained by fitting the polarization curve, which further evaluates the HER reaction kinetics of the catalyst. Ni2P@CoP@NC has a lower Tafel slope value (127.71mV dec -1 ), lower than Ni2P@C (137.8mV dec -1 ) and CoP@NC(128.4mV dec -1 ), indicating faster HER kinetics. The lower overpotential and Tafel slope indicate the synergistic catalytic effect between the components, and also indicate that P vacancies can reduce the H* / OH* adsorption energy. Figure c further summarizes the overpotentials and corresponding Tafel slopes of the five electrocatalysts. In order to evaluate the durability of Ni2P@CoP@NC catalytic materials for HER in alkaline electrolytes, constant potential chronometry curves were recorded (Figure d). At a current density of 10 mA cm -2 In the case of NC, there is no obvious change in the overpotential after 12 hours of continuous testing, indicating that Ni2P@CoP@NC has good catalytic stability.

[0119] Figure 5In the figure, (a) is the OER polarization curves of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 of the present invention and Comparative Examples 1, 2, 4, and 5; (b) is the Tafel slope of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 of the present invention and Comparative Examples 1, 2, 4, and 5; (c) is the Tafel slope of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 of the present invention and Comparative Examples 1, 2, 4, and 5 at 20 mA cm -2 Overpotential column and Tafel slope graph under current density; (d) is the double layer capacitance curve (C) of Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF, and RuO2 obtained in Example 1 and Comparative Examples 1, 2, 4, and 5 of the present invention. dl ); (e) is the Nyquist diagram and simulated equivalent circuit diagram of Ni2P@CoP@NC, Ni2P@C, and CoP@NC obtained in Example 1 of the present invention, Comparative Examples 1 and 2; (f) is the Ni2P@CoP@NC obtained in Example 1 of the present invention at 20mAcm -2 Chronoamperometric curves under 1.0M KOH alkaline electrolyte and standard three-electrode system, the OER (oxygen evolution reaction) electrochemical performance of Ni2P@CoP@NC multi-shell hollow materials and control samples Ni2P@C, CoP@NC and precious metal catalyst RuO2 were evaluated. As shown in Figure a: an obvious oxidation peak appears at 1.4V vs. RHE, which may be due to the influence of the redox reaction of nickel ions and cobalt ions. In order to eliminate the influence of the oxidation peak on the overpotential, the current density is selected to be 20mAcm -2 The overpotential (η 20 ) as the standard for evaluating the OER performance of the material. The results in Figure a show that at a current density of 20 mA cm -2 When the current density is 200 mA cm, the overpotential of Ni2P@CoP@NC is only 293 mV, which is significantly lower than that of Ni2P@C (318 mV) and CoP@NC (328 mV) with single-layer hollow structures. As shown in Figure a, the advantage of Ni2P@CoP@NC becomes more obvious with the increase of current density. -2 At high current density, the catalytic activity of Ni2P@CoP@NC is close to the OER performance of commercial RuO2. The multiple components in Ni2P@CoP@NC are conducive to the redistribution of electron density and local atomic rearrangement, thereby effectively regulating the electronic structure and coordination environment of the material. At the same time, electron rearrangement is conducive to the transfer of charge on the active site from the electrode interface to the adsorbed reactants. The Tafel slopes of different catalysts obtained by fitting the polarization curves are shown in Figure b. Ni2P@CoP@NC has a lower Tafel slope of 115.15 mV dec.-1 The Tafel slopes of the comparative samples Ni2P@C and CoP@NC are 171.09 mV dec -1 and 121.47mV dec -1 This further proves that Ni2P@CoP@NC has faster reaction kinetics in OER reaction. In order to make the comparison more obvious, 20mA cm -2 The overpotential (η) at the current density 20 ) and the corresponding Tafel slope are plotted as a bar graph as shown in Figure c. The EIS study results also prove that the electrode has good electrochemical performance. ct The smaller the value, the faster the charge transfer between the catalyst and the electrolyte. As can be seen from Figure e, the charge transfer resistance (R ct ) is the smallest among all samples. This indicates that a rapid electron transfer process occurs at the interface between the multi-shell hollow structure Ni2P@CoP@NC and the electrolyte under alkaline conditions, which has faster charge transfer efficiency and higher electrochemical efficiency. The VT curve (Figure f) was obtained after continuous discharge for 12 hours. During the 12-hour discharge process, the potential of Ni2P@CoP@NC remained stable. The excellent durability of Ni2P@CoP@NC may be attributed to the unique hollow structure and the protective effect of the nitrogen-doped carbon shell, which avoids the aggregation of catalytic substances and the shedding of samples during the reaction, thereby ensuring its long-term stability.

[0120] Figure 6 In the figure, (a) is the oxygen evolution reaction cyclic voltammogram of Ni2P@CoP@NC obtained in Example 1 of the present invention; (b) is the oxygen evolution reaction cyclic voltammogram of Ni2P@C obtained in Comparative Example 1 of the present invention; (c) is the oxygen evolution reaction cyclic voltammogram of CoP@NC obtained in Comparative Example 2 of the present invention; (d) is the oxygen evolution reaction cyclic voltammogram of NF obtained in Comparative Example 4 of the present invention; (e) is the oxygen evolution reaction cyclic voltammogram of RuO2 obtained in Comparative Example 5 of the present invention. In order to further study the inherent catalytic activity of Ni2P@CoP@NC multi-shell hollow material catalyst, the double layer capacitance (C dl ), and the electrochemically active surface area (ECSA) of the samples was estimated. The cyclic voltammograms of the five samples are shown in the figure, namely Ni2P@CoP@NC, Ni2P@C, CoP@NC, NF and commercial RuO2. dl The curves and the CV graphs of each material in Figure ae show that the CV cycle of the catalyst increases uniformly at different scan rates, and the C of the Ni2P@CoP@NC catalyst increases with the speed of the CV cycle. dl The value is 25.31mF cm -2, except for commercial RuO2, the closed curve area formed by the CV graph of Ni2P@CoP@NC is the largest, which is conducive to the effective combination with the OER reaction intermediate M-OH, further improving the catalytic activity. This further shows that Ni2P@CoP@NC, due to its special multi-shell hollow structure and P vacancies, provides a large number of active sites, allowing the catalyst to fully contact the electrolyte, increasing the catalytic reaction active area, and providing a channel for O2 overflow during the oxygen evolution reaction.

[0121] Figure 7 In the figure, (a) is the polarization curve of the electrolytic cell of Ni2P@CoP@NC / / Ni2P@CoP@NC obtained in Example 1 of the present invention, and Pt / C / / RuO2 obtained in Comparative Examples 3 and 5; (b) is the full water splitting stability of Ni2P@CoP@NC / / Ni2P@CoP@NC obtained in Example 1 of the present invention, and Pt / C / / RuO2 obtained in Comparative Examples 3 and 5. In view of the excellent HER and OER catalytic activity of Ni2P@CoP@NC, its overall water splitting activity in 1M KOH solution was further evaluated by using a dual-electrode configuration and Ni2P@CoP@NC catalyst as cathode and anode. A commercial Pt / C / / RuO2 electrode was also tested for comparison. As shown in Figure a, during the electrolysis process, a large number of bubbles (inset) are generated at the cathode (H2) and the anode (O2), and Ni2P@CoP@NC / / Ni2P@CoP@NC only requires a voltage of 1.62V to reach 10mAcm -2 The current density is slightly higher than that of Pt / C / / RuO2 electrode (1.59 V). Figure b shows that the electrolysis system exhibits good stability within 12 hours.

[0122] In summary, Ni2P@CoP@NC multi-shell hollow materials have high conductivity and fast electron transfer rate. The efficient synergistic effect of its multiple components makes it rich in active sites, has excellent electrocatalytic performance and long-term stability, and is a candidate catalyst with great application potential for electrocatalytic water splitting.

[0123] Example 2

[0124] This embodiment provides a method for preparing Ni2P@CoP@NC, the steps comprising:

[0125] (1) Preparation of precursor nickel-based glycerate spheres (Ni-gly): 0.14 g Ni(NO3)2·6H2O was added to 20 mL isopropanol, and after being dispersed uniformly by ultrasound, 4 mL glycerol and 1 mL water were added respectively. After stirring for 20 minutes, the mixture was transferred to a 50 mL Telfon-lined autoclave and reacted in an oven at 180°C for 15 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and finally dried in a vacuum oven. The collected product was Ni-gly microspheres.

[0126] (2) Preparation of ZIF-67 coated Ni-gly microsphere composite structure (Ni-gly@ZIF-67): Take 40 mg of Ni-gly and disperse it in 40 mL of ethanol. Pour 10 mL of phytic acid ethanol solution (volume ratio of 1:40) into the above dispersion and stir for 2 hours. This process is to activate the Ni-gly microspheres. Then wash them with ethanol and methanol respectively, and then directly disperse them in 25 mL of methanol after washing. Add 1 g of polyvinyl pyrrolidone (PVP) and stir for 10 minutes, and let it stand for 15 minutes. Dissolve 0.20 g of Co(NO3)2·6H2O in 30 mL of methanol to prepare solution A, and dissolve 2.96 g of dimethylimidazole (2-MIM) in 60 mL of methanol to prepare solution B. Pour solutions A and B into the above-mentioned stationary solutions respectively and stir them together for 2.5 hours. After centrifugation, washing with methanol and drying, purple powder of ZIF-67-coated Ni-gly microspheres was obtained, which was recorded as Ni-gly@ZIF-67.

[0127] (3) Preparation of Ni-gly@ZIF-67-TA multi-shell hollow nanoparticles: 100 mg of Ni-gly@ZIF-67 powder was dissolved in 5 mL of water and dispersed evenly by ultrasonication. 6 mL of tannic acid (TA) solution (24 mmol / L) was adjusted to pH 8 with KOH solution (6 mol / L). The pH-adjusted solution was added dropwise to the above solution and magnetically stirred for 10 min at room temperature to obtain Ni-gly@ZIF-67-TA. The solution was centrifuged, washed with ethanol and water, respectively, and dried in a vacuum oven at 60 °C.

[0128] (4) Preparation of Ni2P@CoP@NC: 300 mg of sodium hypophosphite and 35 mg of Ni-gly@ZIF-67-TA powder were placed in a porcelain boat. The sodium hypophosphite was placed at the upper end of the airflow and the Ni-gly@ZIF-67-TA powder was placed at the lower end of the airflow. The mixture was calcined at 400°C for 2 h at a heating rate of 2°C / min under N2 atmosphere to obtain a black powder, which was recorded as Ni2P@CoP@NC.

[0129] Example 3

[0130] This embodiment provides a method for preparing Ni2P@CoP@NC, the steps comprising:

[0131] (1) Preparation of precursor nickel-based glycerate spheres (Ni-gly): 0.07 g Ni(NO3)2·6H2O was added to 20 mL isopropanol, and after being dispersed uniformly by ultrasound, 4 mL glycerol and 1 mL water were added respectively. After stirring for 20 minutes, the mixture was transferred to a 50 mL Telfon-lined autoclave and reacted in an oven at 190°C for 15 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and finally dried in a vacuum oven. The collected product was Ni-gly microspheres.

[0132] (2) Preparation of ZIF-67 coated Ni-gly microsphere composite structure (Ni-gly@ZIF-67): Take 40 mg of Ni-gly and disperse it in 40 mL of ethanol. Pour 10 mL of phytic acid ethanol solution (volume ratio of 1:40) into the above dispersion and stir for 2 hours. This process is to activate the Ni-gly microspheres. Then wash them with ethanol and methanol respectively, and then directly disperse them in 25 mL of methanol after washing. Add 1 g of polyvinyl pyrrolidone (PVP) and stir for 10 minutes, and let it stand for 15 minutes. Dissolve 0.20 g of Co(NO3)2·6H2O in 30 mL of methanol to prepare solution A, and dissolve 2.96 g of dimethylimidazole (2-MIM) in 60 mL of methanol to prepare solution B. Pour solutions A and B into the above-mentioned stationary solutions respectively and stir them together for 2.5 hours. After centrifugation, washing with methanol and drying, purple powder of ZIF-67-coated Ni-gly microspheres was obtained, which was recorded as Ni-gly@ZIF-67.

[0133] (3) Preparation of Ni-gly@ZIF-67-TA multi-shell hollow nanoparticles: 100 mg of Ni-gly@ZIF-67 powder was dissolved in 5 mL of water and dispersed evenly by ultrasonication. 6 mL of tannic acid (TA) solution (24 mmol / L) was adjusted to pH 8 with KOH solution (4 mol / L). The pH-adjusted solution was added dropwise to the above solution and magnetically stirred for 10 min at room temperature to obtain Ni-gly@ZIF-67-TA. The solution was centrifuged, washed with ethanol and water, respectively, and dried in a vacuum oven at 60 °C.

[0134] (4) Preparation of Ni2P@CoP@NC: 320 mg of sodium hypophosphite and 35 mg of Ni-gly@ZIF-67-TA powder were placed in a porcelain boat. The sodium hypophosphite was placed at the upper end of the airflow and the Ni-gly@ZIF-67-TA powder was placed at the lower end of the airflow. The mixture was calcined at 380°C for 2 h at a heating rate of 2.5°C / min under N2 atmosphere to obtain a black powder, which was recorded as Ni2P@CoP@NC.

[0135] Example 4

[0136] This embodiment provides a method for preparing Ni2P@CoP@NC, the steps comprising:

[0137] (1) Preparation of precursor nickel-based glycerate spheres (Ni-gly): 0.07 g Ni(NO3)2·6H2O was added to 20 mL isopropanol, and after being dispersed uniformly by ultrasound, 4 mL glycerol and 1 mL water were added respectively. After stirring for 20 minutes, the mixture was transferred to a 50 mL Telfon-lined autoclave and reacted in an oven at 200°C for 15 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with ethanol, and finally dried in a vacuum oven. The collected product was Ni-gly microspheres.

[0138] (2) Preparation of ZIF-67 coated Ni-gly microsphere composite structure (Ni-gly@ZIF-67): 40 mg of Ni-gly was dispersed in 40 mL of ethanol, and 10 mL of phytic acid ethanol solution (volume ratio of 1:40) was poured into the above dispersion and stirred for 2 hours. This process is to activate the Ni-gly microspheres. Then, they were washed with ethanol and methanol respectively, and directly dispersed in 25 mL of methanol after washing. 10 g of polyvinyl pyrrolidone (PVP) was added and stirred for 10 minutes, and then allowed to stand for 15 minutes. 0.40 g of Co(NO3)2·6H2O was dissolved in 30 mL of methanol to prepare solution A, and 3.12 g of dimethylimidazole (2-MIM) was dissolved in 60 mL of methanol to prepare solution B. Solutions A and B were poured into the above-mentioned stationary solutions respectively and stirred together for 2.5 hours. After centrifugation, washing with methanol and drying, purple powder of ZIF-67-coated Ni-gly microspheres was obtained, which was recorded as Ni-gly@ZIF-67.

[0139] (3) Preparation of Ni-gly@ZIF-67-TA multi-shell hollow nanoparticles: 100 mg of Ni-gly@ZIF-67 powder was dissolved in 5 mL of water and dispersed evenly by ultrasonication. 6 mL of tannic acid (TA) solution (24 mmol / L) was adjusted to pH = 10 with KOH solution (5 mol / L). The pH-adjusted solution was added dropwise to the above solution and magnetically stirred for 10 min at room temperature to obtain Ni-gly@ZIF-67-TA. The solution was centrifuged, washed with ethanol and water respectively, and dried in a vacuum oven at 60 °C.

[0140] (4) Preparation of Ni2P@CoP@NC: 300 mg of sodium hypophosphite and 30 mg of Ni-gly@ZIF-67-TA powder were placed in a porcelain boat. The sodium hypophosphite was placed at the upper end of the airflow and the Ni-gly@ZIF-67-TA powder was placed at the lower end of the airflow. The mixture was calcined at 350°C for 2 h at a heating rate of 2°C / min under N2 atmosphere to obtain a black powder, which was recorded as Ni2P@CoP@NC.

[0141] The Ni2P@CoP@NC obtained in Example 2-4 was characterized by XRD. Its diffraction pattern showed peaks at 40.8°, 44.6°, 47.3°, 54.2°, 54.9° and 74.7°, corresponding to the (111), (201), (210), (300), (211) and (400) crystal planes of Ni2P; and peaks at 31.6°, 36.3°, 46.2°, 48.1° and 56.8°, corresponding to the (011), (111), (112), (211) and (301) crystal planes of CoP. The results show that Ni2P and CoP coexist in the samples synthesized in Example 2-4 of the present invention, which are composite materials of Ni2P and CoP.

[0142] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A method for preparing an electrocatalyst, characterized in that the steps include: Provide a Ni-gly microsphere; Mixing Ni-gly microspheres, cobalt salt, and 2-methylimidazole in a first solvent to obtain Ni-gly@ZIF-67; Ni-gly@ZIF-67 was etched with tannic acid to obtain Ni-gly@ZIF-67-TA; Ni-gly@ZIF-67-TA is phosphated to obtain Ni2P@CoP@NC, i.e., the composite electrocatalyst.

2. The preparation method according to claim 1, wherein the preparation method of the Ni-gly microspheres comprises: The nickel salt and glycerol are mixed and reacted in a second solvent to obtain Ni-gly microspheres.

3. The preparation method according to claim 1, wherein the Ni-gly microspheres are activated before being mixed with the cobalt salt and 2-methylimidazole; in, The activation of the Ni-gly microspheres comprises the following steps: The Ni-gly microspheres were mixed with an ethanol solution of phytic acid to obtain activated Ni-gly microspheres.

4. The preparation method according to claim 3, wherein in the ethanol solution of phytic acid, the volume ratio of phytic acid to ethanol is 1:(20-80), preferably 1:(30-60), preferably 1:(40-50); and / or The activation time is 1-5h, preferably 1-4h, more preferably 2-3h; and / or The activation temperature is -10-50°C, preferably -5-40°C, more preferably 0-35°C.

5. The preparation method according to claim 1, wherein the Ni-gly microspheres, cobalt salt and 2-methylimidazole are mixed in a first solvent, the steps comprising: The Ni-gly microspheres are first mixed in a portion of the first solvent to obtain a first solution; Mixing cobalt salt and 2-methylimidazole in a portion of the first solvent to obtain a second solution; The first solution is mixed with the second solution.

6. The preparation method according to claim 1, wherein the tannic acid etches Ni-gly@ZIF-67, the steps comprising: Dispersing Ni-gly@ZIF-67 in a third solvent to obtain a third solution; providing a solution of tannic acid dispersed in a third solvent, i.e., a tannic acid solution; adding alkali to the tannic acid solution and adjusting the pH value to a preset value to obtain a fourth solution; The fourth solution is added to the third solution to react and obtain the Ni-gly@ZIF-67-TA.

7. The preparation method according to claim 6, wherein the preset pH value is 7-14, preferably 8-12, and more preferably 8-10; and / or The fourth solution is added to the third solution in a dropwise manner.

8. The preparation method according to claim 1, wherein the phosphating step comprises: Calcine Ni-gly@ZIF-67-TA and phosphate in a closed environment to obtain Ni2P@CoP@NC, i.e., the composite electrocatalyst; preferably, The mass ratio of the Ni-gly@ZIF-67-TA to phosphate (with P as the standard) is 1:(2-15), preferably 1:(4-12), and more preferably 1:(6-10).

9. An electrocatalyst, characterized in that Its structure is Ni2P@CoP@NC, and it is obtained based on the preparation method described in any one of claims 1-8.

10. Use of the electrocatalyst according to claim 9, characterized in that: The electrocatalyst can be applied to water electrolysis, especially hydrogen evolution and / or oxygen evolution reaction.